CEO EDUCATION ON FIRM PERFORMANCE: MEDIATION ANALYSIS THROUGH CORPORATE SOCIAL RESPONSIBILITY - Ni Luh Putu Normadewi Abdi Pradnyani; Alfa Rahmiati; I Nyoman Abdi; Anak Agung Putu Agung Purnama Sari (Jurnal Bisnis dan Akuntansi, 2026)
The role of a CEO is critical in shaping an organization's strategic direction, as the decisions made by CEOs strongly influence corporate growth and long-term performance. In addition, the implementation of CSR has become an important strategic initiative that may enhance both organizational sustainability and financial outcomes. This study examines the effect of CEO education on firm performance by considering three dimensions of educational background, namely educational attainment, field of study, and overseas education. Furthermore, CSR is incorporated as a mediating variable to explain the mechanism through which CEO education affects organizational performance. This research offers additional insight into the literature by highlighting how CEOs' educational characteristics contribute to the effectiveness of CSR implementation. This research examines energy sector companies that were listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021. Using a sample of 47 firms with a total of 235 firm-year observations, the hypotheses were tested using STATA statistical software. The findings reveal that higher CEO educational qualifications, relevant academic specialization, and international educational experience is related to better CSR implementation and better company performance. Companies managed by CEOs with stronger educational backgrounds, industry-related expertise, or overseas education tend to achieve superior organizational performance. The analysis found that CSR plays a partial role in linking CEO education to firm performance. These findings suggest that appointing highly educated CEOs and strengthening CSR implementation can support the achievement of better corporate performance.